Introduction to environmental impact assessment - Glasson, John.; Therivel, Riki.; Chadwick, Andrew ([S.l.] : Routledge, 2010)
A revised text featuring more case studies, illuminating the role of consultants, clients, local authorities and environmental agencies in the EIA process, and procedures and conventions for assessment arising out of changes in the legal and.